Creative action research. Issue 4 (8th August 2021) - Cox, Robin; Heykoop, Cheryl; Fletcher, Sarah; Hill, Tiffany; Scannell, Leila; Wright, Laura; Alexander, Kiana; Deans, Nigel; Plush, Tamara
ABSTRACT: Youth-Creative Action Research (Y-CAR) is a variant of participatory action research specifically suited for exploring and developing evidence-informed innovations to address complex social challenges such as climate change. In this paper, we present an overview of Y-CAR and explore its core defining features, potential for application in research and action, and connection to other action-oriented research methodologies. We draw on a range of examples of this emergent methodology that illustrates its evolution and core principles in action and show how it has been implemented in research. We conclude the paper by examining key learnings, future leverage points, and limitations to applying Y-CAR in practice.